Functional Outcome of Cementless Total Hip Replacement in Avascular Necrosis Head of Femur. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the early functional outcome of cementless total hip replacement (THR) in patients with avascular necrosis head of femur.Methods: This descriptive study was conducted in Department of Orthopedic Surgery Unit I Services Hospital Lahore from 5th August 2018 to 10th September 2021. All adults patients of both gender with avascular necrosis of head of femur fulfilling the inclusion criteria were operated with cementless total hip replacement (THR). Post operative functional outcome at 3, 6 and 12 months was determined with Harris Hip Score(HHS) and compared with pre operative HHS. P value was calculated with paired t-test. P value < 0.05 was considered significant. HHS was graded excellent (90 to 100), good (80 to 90), fair (70 to 80) and poor (